The role and mechanism of compressive stress in tumor - Tan, Min; Song, Bingqi; Zhao, Xinbin; Du, Jing (Frontiers in Oncology, 2024)
Recent research has revealed the important role of mechanical forces in the initiation and progression of tumors. The interplay between mechanical and biochemical cues affects the function and behavior of tumor cells during the development of solid tumors, especially their metastatic potential. The compression force generated by excessive cell proliferation and the tumor microenvironment widely regulates the progression of solid tumor disease. Tumor cells can sense alterations in compressive stress through diverse mechanosensitive components and adapt their mechanical characteristics accordingly to adapt to environmental changes. Here, we summarize the current role of compressive stress in regulating tumor behavior and its biophysical mechanism from the mechanobiological direction.